INTERPRETASI SPACE OF CONSUMPTION DALAM INTERIOR MAL - Subandinah, - (Jurnal Ilmiah Widya, 2018)
Spaces of consumption are a concept of a cultural society that came about in the wake of industrial revolution. Shopping centres, build in every city in every corner of world, are packed with visitors and buyers. The developments of shopping centres with engineered interior are done to entice people to come and shop, and gaining profit from them. Engineered interior is a part of architecture which studies how to create a space for activity; this includes spaces in shopping centres. Interpretation has a lot of definition, some of them are: explanation, decode, represent. The goal of this study is to interpret the space of consumption in a shopping centre. Semiotic approach, with sign system, shall be used as an interpretation reading tool through literature review, observation and qualitative research. The result of the study are: (1) a deeper understanding of space consumption will have huge impact to the current and future lifestyle. (2) The study can also be used by government official in terms of city planning, shopping centre placement that benefitted all individuals and societies.